Cytomegalovirus induction of tumor necrosis factor-alpha by human monocytes and mucosal macrophages. - P D Smith; S S Saini; M Raffeld; J F Manischewitz; S M Wahl (The Journal of Clinical Investigation, 1992)
Cytomegalovirus (CMV) is a major cause of inflammatory organ disease in immunosuppressed persons. To elucidate the mechanisms of CMV-induced inflammation, we investigated whether tumor necrosis factor-alpha (TNF-alpha) was involved in the pathogenesis of CMV colitis in patients with AIDS. In in situ hybridization experiments, TNF-alpha mRNA was shown to be abundantly present in colonic mucosa from AIDS patients with CMV colitis but not in colonic mucosa from control (AIDS and normal) subjects. The TNF-alpha transcripts, identified in macrophage-like cells containing cytomegalic inclusions, were positively associated with CMV, but not HIV-1, within the mucosa. In in vitro experiments, a patient-derived isolate of CMV, but not HIV-1Ba-L, induced human monocytes to express TNF-alpha mRNA and to release increased levels of TNF-alpha peptide following stimulation. CMV induction of TNF-alpha may play a critical role in CMV-induced inflammation and, since TNF-alpha upregulates expression of HIV-1, offers a mechanism by which CMV could serve as a co-factor for HIV-1 expression without both viruses infecting the same cell. Images